(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
The aim of this report is to present various clinical and radiological features of a young female patient with tuberous sclerosis who exhibited multiple hamartomas of various organ system. Tuberous sclerosis is a rare neurocuteneous syndrome exhibiting multiple hamartomatous proliferations that may involve multiple organ system such as brain, kidney, heart, lungs, eyes and skin. An 18 year old female patient presented with abdominal pain and swelling. Clinical examination of the patient revealed presence of facial angiofibromas and huge left flank mass. She also gave history of twin pregnancy with IUD. USG of abdomen showed bilateral gross angiomyolipoma with necrosis and haemorrhage in left kidney. CT and MRI of brain showed presence of multiple cortical tubers and calcified subependymal nodules. This case report is a good example of complex nature of tuberous sclerosis. The diagnosis and management of these patients depend on the presentation of the disease. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.21044